How transactive memory systems and reflexivity relate with innovation in healthcare teams - Marques-Quinteiro, P.; Curral, L.; Passos, A. M.; Lewis, K.; Gomes, C. (Análise Psicológica, 2019)
Transactive memory systems promote the effective exchange of diverse information, and may therefore contribute to healthcare teams innovation. PrioOs sistemas de memória transitiva promovem a troca eficiente de informação, contribuindo para a inovação das equipas hospitalares. Estudos anteriores sugerem que os sistemas de memória transitiva podem ser mais úteis para tarefas repetitivas. Neste estudo, conciliamos estes resultados contraditórios argumentando que as eficiências de processamento dos sistemas de memória transitiva beneficiarão a inovação, porque os sistemas de memória transitiva ajudarão os membros da equipa a refletirem sobre os seus processos e metas. A amostra deste estudo incluiu 256 enfermeiros hospitalares (N=54 equipas). Os resultados sugerem que a reflexividade medeia positivamente a relação entre os sistemas de memória transitiva e a inovação das equipas. Este estudo contribui para a literatura ao clarificar de que forma é que as estruturas e processos cognitivos das equipas se combinam para influenciar a inovação das equipas hospitalares; e para a prática ao oferecer ideias para a gestão de equipas em ambiente hospitalar.r research on performance outcomes, however, suggests that transactive memory systems might be most useful for repetitive, rather than novel tasks. We reconcile these conflicting predictions by arguing that the information processing efficiencies of a transactive memory system will benefit innovation because transactive memory systems will help team members also reflecting on their processes and goals. We tested our hypotheses in a sample of 256 healthcare nurses (Nteams=54). Our findings support prior research showing that reflexivity is positively related to team innovation in teams. Furthermore, we found that reflexivity fully mediates the relationship between transactive memory systems and team innovation. This study contributes to the literature by addressing how team cognitive structures and processes combine to affect innovation. This study makes practical contributions by offering ideas for organizing in healthcare settings.